An ontology to document a quality scheme specification of a software product. Issue 5 (8th May 2017) - Blas, María Julia; Gonnet, Silvio; Leone, Horacio
Abstract: Pressman's (2010) definition of software quality is the conformance to explicitly stated functional and performance requirements, explicitly documented development standards, and implicit characteristics that are expected of all professionally developed software. The achievement of quality is a complex activity that is related with the process quality and product quality. However, still, it is not clear how product quality should apply in the development process. Frequently, the development team does not know what characteristics influence a specific entity and how these characteristics compose the quality of the product. This lack of knowledge reflects the need to define some document that serve as a valid quality specification that should be evaluated along the development process. This contribution addresses this need by introducing an ontology for document a quality scheme based on the product quality model of ISO/IEC 25010. The proposal follows this model with aims to clarify the properties that are normally present in a product and its meaning. The ontology incorporates the metric concept to represent the way in which quality should be measure. The ontology was implemented using Protégé, and it was evaluated using a set of metrics that estimate the required structural characteristics.